Factor Responsible for Surgical Site Infection Following Emergency Non-Traumatic Abdominal Surgery - Yadav, Aditya Prakash; Rauniyar, Chandrika Sah; Joshi, Manisha; Singh, Ajit; Shrestha, Brijesh (Med Phoenix, 2023)
Introduction: Surgical Site Infection (SSI) have always been a major complication of surgery. It results from microbialinfection during or after the surgical procedure. According to CDC, SSI can be classified as superficial,deep and organ/ space. It increases morbidity and also increases cost to the patient and healthcare system. The aim of this study is to determine the factors responsible for surgical site infection following emergency non- traumatic abdominal surgery.Materials and Methods: This prospective study was carried out in Department of Surgery of National Medical College and Teaching Hospital. A total of 90 patients were included in this study. Data analysis was done using SPSS (Statistical Package for social sciences), version 26.Results: Mean age of the study population was 42.74 years. The majority of the subjects were in the age group of 31-40 years. Most of the patients were males (68.8%). The commonest pathology for undertaking operation was Perforated Duodenal ulcer (42.2%).Preoperative serum albumin level, Smoking, comorbidity like COPD, Hypertension, DM, BMI showed statistical relation to surgical site infection.Conclusion: Numerous host factors like malnutrition, obesity, co-morbidity, type of wounds, time of presentation, personal habit contribute to increased incidence of SSI.